Patterns of Change in 18th-Century English : A Sociolinguistic Approach. - Nevalainen, Terttu. (Advances in Historical Sociolinguistics Series, 2018)
Eighteenth-century English is often associated with normative grammar. But to what extent did prescriptivism impact ongoing processes of linguistic change? Basing their work on a variationist sociolinguistic approach, the authors introduce models and methods used to trace the progress of linguistic changes in the "long" 18th century, 1680-1800.